A educação dos trabalhadores do campo no IFRS - Campus Sertão: do escrito ao realizado - Salomão, Elaine Pires (2017)
This text presents the following study “The Education of rural workers at IFRS – Campus Sertão: from written to accomplished”, which aimed to develop impressions concerning professional educational politics, associated with the countryside education politics, amidst existing tensions between the concepts of countryside education and rural education and confront the countryside education politics with the practices arose from professional education targeted at field workers, recognizing the proximity and distance between these realities. Concerning the approach, the paper was based in a qualitative research, of a documentary nature and through the organization of focused groups alongside students from the students of the secondary education integrated to professional and technological education in Agriculture, from 1st ans 3rd years, aiming to shed light on the speeches, which were silenced and/or institutionalized, about the routine of the politics of professional education from the countryside education perspective. The theoretical foundation of this paper was mainly based on the coming authors: Rodeli Caldart, Conceição Paludo, Paulo Freire, Miguel Arroyo, Silvana Gritti, Gaudêncio Frigotto. The study signaled the challenges of the reality of life and professional formation of workers whether of the field or the city. It was yet confirmed that the education of field workers, specially of IFRS – Campus Sertão, must focus on the formation targeted at an education that combines agriculture and ecology, as well as the technical-scientific potential of the students, so that their practices lead to actions of technical assistance and rural extension, in a perspective that assures the social, environmental and economical sustainability of rural lands. At last, the possibility of overcoming the ties related to the Rural Education and the presentation of alternatives to building a more sustainable world, where education is effectively understood as a right of the countryside peoples were evidenced.